1985
DOI: 10.1007/bf00395897
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature and light on the toxicity and growth of the blue-green alga Microcystis aeruginosa (UV-006)

Abstract: The toxicity and growth of Microcystis aeruginosa (UV-006) from the Hartbeespoort Dam, South Africa were investigated at different temperatures and photon fluence rates under laboratory conditions. Cells harvested in late logarithmic growth phase were most toxic when grown at 20°C (LD50) median lethal dose [IP, mouse]=25.4 mg kg(-1)). Toxicity was markedly reduced at growth temperatures above 28° C. Fluence rate had a smaller effect on the toxicity of the cells, but toxicity tended to be less at the very low a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
126
1
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(143 citation statements)
references
References 20 publications
14
126
1
2
Order By: Relevance
“…The production of [D-Leu 1 ] MC-LR decreased with increasing temperature, coinciding with the findings of Gorham, 1964;Runnegar et al, 1983;van der Westhuizen and Eloff, 1985;Cood and Poon, 1988;Sivonen, 1990;Rapala et al, 1997;Lehman et al, 2008;Wang et al, 2010 andGiannuzzi et al (2016). van der Westhuizen and Eloff (1985) reported that the optimal growth conditions do not coincide with the production of toxins.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…The production of [D-Leu 1 ] MC-LR decreased with increasing temperature, coinciding with the findings of Gorham, 1964;Runnegar et al, 1983;van der Westhuizen and Eloff, 1985;Cood and Poon, 1988;Sivonen, 1990;Rapala et al, 1997;Lehman et al, 2008;Wang et al, 2010 andGiannuzzi et al (2016). van der Westhuizen and Eloff (1985) reported that the optimal growth conditions do not coincide with the production of toxins.…”
Section: Discussionsupporting
confidence: 73%
“…van der Westhuizen and Eloff (1985) reported that the optimal growth conditions do not coincide with the production of toxins. Similarly, Gorham (1964) affirmed that the optimum temperature for growth (30 C -35 C) differed from that for optimal toxicity (25 C).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that secondary metabolites are produced by diverse cyanobacteria encompassing varied ecological niches, it is plausible that microcystin synthesis is associated with and/or regulated by environmental factors affecting cell metabolism, growth, and ultimately, abundance . Reports that state microcystin production and/ or cell quota are influenced by select abiotic parameters, including temperature, irradiance, macro/micronutrients, and pH (van der Westhuizen and Eloff 1985;Lukac and Aegerter 1993;Song et al 1998;Downing et al 2005), support this premise.…”
Section: Introductionmentioning
confidence: 98%